Relationship of Completeness of Filling Out a Medical Resume with Accuracy of Secondary Diagnosis Codes of Surgical Inpatients - Darmining; Windatania Mayasari; Dafrosa Luni; Aldina Ruwari; Gradiana Tafuli (CV. Get Press Indonesia, 2025)
Coding is an important part of medical records management, significantly affecting reporting accuracy and insurance claim. It was found that incomplete filling of medical resumes by medical personnel caused inaccuracies, especially in secondary diagnosis coding. This study aims to examine the relationship between the completeness of the filling of medical resumes with the accuracy of the secondary diagnosis code in the medical record of surgical hospitalization. Using a descriptive quantitative analytical approach, data were collected through observation of 84 medical records. The observation table served as a research instrument, with the data analyzed by the bivariate method, and The chi-square was used for statistical testing. Results showed 29 records (34.5%) had incomplete medical resumes, while 35 records (41.7%) contained inaccuracies in secondary diagnosis coding. Statistical analysis confirmed a significant relationship between the completeness of medical resumes and the accuracy of secondary diagnosis codes (p = 0.000). These findings suggest that incomplete resume filling negatively affects the quality of secondary diagnosis coding, compromising the validity of medical record data and hospital administrative processes. The study concludes that medical personnel must ensure complete filling of medical resumes to improve coding accuracy and enhance overall hospital record quality.